N-acetylcysteine potentiates diclofenac toxicity in Saccharomyces cerevisiae: stronger potentiation in ABC transporter mutant strains. (2nd January 2018) - Al-Attrache, Houssein; Chamieh, Hala; Hamzé, Monzer; Morel, Isabelle; Taha, Samir; Abdel-Razzak, Ziad
Abstract: Diclofenac (DCF) adverse reactions involve diverse mechanisms in different models. We recently demonstrated that DCF-induced toxicity in HepaRG decreases as they express DCF-metabolizing enzymes. DCF metabolism promotes toxicity in Saccharomyces cerevisiae expressing heterologous cytochromes-P450. N-Acetylcysteine (NAC) is used to treat diverse medical conditions due to its multiple properties (antioxidant, metal chelator, thiol-disulfide disruption). The latter property accounts for its mucolytic effects and broadens its potential molecular targets to signal transduction proteins, ABC transporters and others. Interaction of NAC with DCF effects depends on the experimental model. This study aims to investigate NAC/DCF interaction and the involvement of ABC transporters in wild type and mutant Saccharomyces cerevisiae . DCF inhibited yeast growth in a dose- and time-dependent manner and the cells started adapting to DCF 24-h post-treatment. NAC potentiated DCF-induced toxicity if added prior or parallel to DCF. Pretreatment with NAC increased its potentiation effect and compromised cells adaption to DCF. Post-treatment with NAC potentiated DCF toxicity without compromising adaptation. Moreover, mutant strains in ABC transporters Pdr5, Yor1, Bpt1 or Pdr15, were more sensitive to DCF; while mutant strains in Pdr5, Vmr1 or Pdr12 were more sensitive to NAC/DCF interaction. DCF ± NAC elicited on the mutant strain in Yap1, an oxidative stress-related protein, the same effects as on the wild type. Therefore, oxidative stress does not seem to be key actor in DCF toxicity in our model. Our hypothesis is that NAC potentiation effect is at least due to its ability to disrupt disulfide bridge in proteins required to overcome DCF toxicity in yeast.